Assessment of natal origin of pike (Esox lucius) in the Baltic Sea using Sr:Ca in otoliths - Engstedt, Olof; Stenroth, Patrik; Larsson, Per; Ljunggren, Lars; Elfman, Mikael (Environmental Biology of Fishes, 2010)
Spawning habitat of pike (Esox lucius) in the Baltic Sea include brackish water bays, brooks and rivers. Elevated salinity concentrations are one of several stressors that might increase the use and importance of freshwater habitats for spawning. In the Baltic Sea, one of the largest brackish seas in the world, freshwater species like pike, perch (Perca fluviatilis), whitefish (Coregonus sp), bream (Abramis brama), ide (Leuciscus idus), roach (Rutilus rutilus) and burbot (Lola iota) all undertake spawning migrations to freshwater. However, over the last decades populations densities of these species have declined, and recruitment failure has been argued to be at least part of the problem. The importance of brooks and rivers as spawning areas for these species have not been quantified and set in relation to spawning success in brackish bays. In this study, we collected 175 adult pike (Esox lucius) on their foraging grounds in the sea. Fish were collected in two regions on the Baltic coast, more than 600 km apart. Subsequently we determined their origin (freshwater or marine) using otolith chemistry. Sagittal otoliths were analysed for strontium using the PIXE-method. The results show that 80 of the 175 pike were recruited in freshwater, and several of the larger specimens showed reoccurring migration behaviour. Data show that freshwater is an important recruitment habitat for Baltic Sea pike, suggesting that habitat improvements in rivers entering the Baltic Sea might significantly contribute to population restoration.